Diamond-like carbon film, preparation method thereof and optical lens
By using a diamond-like film with transition layer, hydrophobic layer and protective layer on the infrared lens, the problem of short service life and poor hydrophobic performance in humid environments is solved, and higher hydrophobic performance and longer service life are achieved, while ensuring imaging quality.
Patent Information
- Application Number
- CN202311308768.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
AI Technical Summary
Infrared lenses have a short service life in humid environments and poor hydrophobic performance affects imaging quality.
A diamond-like film is used which is a transition layer, a hydrophobic layer and a protective layer formed in sequence along the substrate surface. The transition layer is an undoped diamond-like film layer, the hydrophobic layer is a fluorinated diamond-like film layer, and the protective layer is a diamond-like film layer. The average transmittance of the film in the infrared band of 8μm-12μm is ≥50%, and the hydrophobic angle is 85°-120°.
It significantly enhances the hydrophobic properties of the surface of the lens material, improves the adaptability to a variety of harsh environments, extends the service life of the lens, and reduces the negative impact of humid environments on imaging quality.
Smart Images

Figure CN119800320A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of optical coatings, and in particular, to a diamond-like film and a preparation method thereof, as well as an optical lens. Background Art
[0002] In recent years, the infrared thermal imaging industry has developed rapidly, and its role in security and other work cannot be ignored. Infrared lenses suitable for various extreme conditions have emerged to meet complex application requirements. However, the life of infrared lenses used in extreme conditions is generally short. For example, infrared lenses used in humid and dark environments, due to the high humidity in the environment, corrosive substances will adhere to the surface of the lens through water vapor and other liquid media. After long-term accumulation, it will cause irreversible corrosion to the surface film and lens, seriously affecting the service life of the lens.
[0003] At present, the exposed surfaces of some infrared lenses use DLC (Diamond-Like Carbon) film. The DLC film has the advantages of good friction resistance and weather resistance, but poor hydrophobicity, which directly affects the service life of the lens and has a negative impact on the imaging quality of the lens.
[0004] Therefore, how to enhance the hydrophobic properties of the surface of infrared lens materials so that they can adapt to a variety of harsh environments and extend the service life of the lens is a technical problem that needs to be solved at present. Summary of the invention
[0005] According to one aspect of the present application, a diamond-like film is provided, comprising a transition layer, a hydrophobic layer and a protective layer sequentially formed along the surface of a substrate, wherein the transition layer comprises at least an undoped diamond-like film layer, and the thickness of the undoped diamond-like film layer is 450nm-1200nm; the hydrophobic layer comprises at least a fluorinated diamond-like film layer, and the thickness of the fluorinated diamond-like film layer is 100nm-600nm; the protective layer comprises at least a diamond-like film layer, and the thickness of the diamond-like film layer is 10nm-30nm; wherein the average transmittance of the diamond-like film in the infrared band of 8μm-12μm is ≥50%.
[0006] In one or more embodiments, the substrate material includes germanium, silicon, or chalcogenide glass.
[0007] In one or more embodiments, the fluorinated diamond-like carbon film layer is formed on the surface of the transition layer by a chemical vapor deposition process.
[0008] In one or more embodiments, the wavelength corresponding to the maximum transmittance of the diamond-like carbon film in the 8 μm-12 μm infrared band is in the range of 9.0 μm-9.9 μm.
[0009] In one or more embodiments, before forming the transition layer, a disordered microstructure is formed on the surface of the substrate.
[0010] In one or more embodiments, the hydrophobic angle of the diamond-like carbon film is 85°-120°.
[0011] According to another aspect of the present application, an optical lens is provided, comprising a substrate, and a diamond-like carbon film as described above formed on the substrate.
[0012] According to another aspect of the present application, a diamond-like film is provided, comprising a transition layer, a hydrophobic layer and a protective layer sequentially formed along the surface of a substrate, wherein the transition layer comprises at least an undoped diamond-like film layer, and the thickness of the undoped diamond-like film layer is 450nm-1200nm; the hydrophobic layer comprises at least a doped diamond-like film layer, and the thickness of the doped diamond-like film layer is 100nm-600nm; the protective layer comprises at least a diamond-like film layer, and the thickness of the diamond-like film layer is 10nm-30nm; wherein the average transmittance of the diamond-like film in the infrared band of 8μm-12μm is ≥50%; the element or material doped in the doped diamond-like film layer is selected from at least one of the following: Fe, Al, Cu, Ag, Sn, Si, Ti, Ge, and an organic polymer.
[0013] According to another aspect of the present application, a method for preparing a diamond-like film is provided, the method comprising: performing surface pretreatment on a substrate and forming a disordered microstructure on the surface of the substrate; forming an undoped diamond-like film layer with a thickness of 450nm-1200nm on the surface of the substrate; forming a fluorinated diamond-like film layer with a thickness of 100nm-600nm on the surface of the undoped diamond-like film layer; and forming a diamond-like film layer with a thickness of 10nm-30nm on the surface of the fluorinated diamond-like film layer.
[0014] In one or more embodiments, the substrate material includes germanium, silicon, or chalcogenide glass.
[0015] In one or more embodiments, the step of performing surface pretreatment on the substrate includes: polishing the surface of the substrate to reduce the surface roughness of the substrate to the nanometer level; increasing the surface roughness of the substrate by laser etching and forming a disordered microstructure on the surface of the substrate; and pre-cleaning the surface of the substrate under vacuum conditions to remove impurities on the surface of the substrate and activate the surface of the substrate.
[0016] In one or more embodiments, the step of forming an undoped diamond-like film layer with a thickness of 450nm-1200nm on the surface of a substrate includes: using hydrocarbon gas as a reaction gas and an inert gas as a working gas, and adopting a plasma enhanced chemical vapor deposition process to form an undoped diamond-like film layer on the surface of the substrate; wherein the hydrocarbon gas includes butane, the inert gas includes argon, and the flow ratio of butane to argon is 2:1 to 4:1.
[0017] In one or more embodiments, the step of forming a fluorinated diamond-like film layer with a thickness of 100nm-600nm on the surface of the undoped diamond-like film layer includes: using fluorine-containing gas and hydrocarbon gas as reaction gases and inert gas as working gas, and adopting a plasma enhanced chemical vapor deposition process to form a fluorinated diamond-like film layer on the surface of the transition layer; wherein the fluorine-containing gas includes carbon tetrafluoride, the hydrocarbon gas includes methane or acetylene, and the flow ratio of carbon tetrafluoride to methane or acetylene is 8:1 to 11:1.
[0018] In one or more embodiments, the step of forming a diamond-like film layer with a thickness of 10 nm to 30 nm on the surface of the fluorinated diamond-like film layer includes: using hydrocarbon gas as a reaction gas and an inert gas as a working gas, and using a plasma enhanced chemical vapor deposition process to form a diamond-like film layer on the surface of the fluorinated diamond-like film layer;
[0019] The hydrocarbon gas includes butane or acetylene, the inert gas includes argon, and the flow ratio of butane or acetylene to argon is 2:1 to 4:1.
[0020] In one or more embodiments, before the step of forming a diamond-like film layer on the surface of the fluorinated diamond-like film layer, it also includes: using argon as a working gas, utilizing an ion source and a bias power supply to form high-energy argon ions to bombard the surface of the fluorinated diamond-like film layer to improve the surface roughness of the fluorinated diamond-like film layer.
[0021] In one or more embodiments, the disordered microstructure is a nanoscale structure.
[0022] The diamond-like carbon film, its preparation method, and the optical lens provided in the embodiments of the present application can greatly enhance the hydrophobic properties of the lens material surface, significantly improve its adaptability to various harsh environments, extend the service life of the lens, and minimize the negative impact of a humid environment on the lens and imaging quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings:
[0024] Figure 1A schematic structural diagram of a diamond-like film provided according to an embodiment of the present application is shown;
[0025] Figure 2 A schematic diagram of a process flow of a method for preparing a diamond-like film according to an embodiment of the present application is shown;
[0026] Figure 3 A schematic diagram of an infrared transmittance curve of a hydrophobic layer according to Embodiment 1 of the present application is shown;
[0027] Figure 4 A schematic diagram showing a hydrophobic angle of a germanium-based DLC film according to the related art;
[0028] Figure 5 A schematic diagram showing the hydrophobic angle of the germanium-based DLC film according to the first embodiment of the present application is shown;
[0029] Figure 6 A schematic diagram of an infrared transmittance curve of a hydrophobic layer according to Embodiment 2 of the present application is shown;
[0030] Figure 7 A schematic diagram showing a hydrophobic angle of a germanium-based DLC film according to the related art; and
[0031] Fig. 8A and Figure 8B Schematic diagrams of the hydrophobic angle of the germanium-based DLC film according to the second embodiment of the present application are respectively shown. DETAILED DESCRIPTION
[0032] In order to better understand the present application, a more detailed description will be made of various aspects of the present application with reference to the accompanying drawings. It should be understood that these detailed descriptions are only descriptions of exemplary embodiments of the present application, and are not intended to limit the scope of the present application in any way. Throughout the specification, the same reference numerals refer to the same elements. The expression "and / or" includes any and all combinations of one or more of the associated listed items.
[0033] It should also be understood that expressions such as "include", "including", "have", "contain" and / or "comprising" are open rather than closed expressions in this specification, which indicate the presence of the stated features, elements and / or components, but do not exclude the presence of one or more other features, elements, components and / or combinations thereof. In addition, when expressions such as "at least one of..." appear after a list of listed features, they modify the entire list of features rather than just the individual elements in the list. In addition, when describing embodiments of the present application, "may" is used to mean "one or more embodiments of the present application". And, the term "exemplary" is intended to refer to an example or illustration.
[0034] Unless otherwise specified, all words (including engineering terms and scientific and technological terms) used in this article have the same meaning as those commonly understood by ordinary technicians in the field to which this application belongs. It should also be understood that, unless clearly stated in this application, words defined in common dictionaries should be interpreted as having the same meaning as their meaning in the context of the relevant technology, and should not be interpreted in an idealized or overly formal sense.
[0035] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. Any one or more embodiments or elements thereof, or the arrangement or combination of some or all embodiments or elements thereof described herein are merely exemplary and are not intended to limit the scope of the present application.
[0036] The features, principles and other aspects of the present application will be described in detail below with reference to the accompanying drawings and in combination with specific implementations.
[0037] Combination Figure 1 As shown, according to one aspect of the present application, a diamond-like carbon film 100 (also referred to as a DLC film 100) is provided, and the DLC film 100 can be used, for example, for optical elements such as infrared highly hydrophobic optical lenses. The DLC film 100 includes a substrate 110, and a transition layer 120, a hydrophobic layer 130, and a protective layer 140 sequentially formed along a surface of one side of the substrate 110.
[0038] According to the diamond-like carbon film provided in the embodiment of the present application, the substrate 110 may be a germanium-based or silicon-based substrate, such as single crystal germanium or single crystal silicon, or may be a chalcogenide glass substrate.
[0039] In an exemplary embodiment, the transition layer 120 includes at least one undoped DLC film layer with a thickness of 450nm-1200nm. Since there is a difference in the structure of the doped DLC film layer and the original film layer, the introduction of the transition layer 120 can ensure that the film layer is firmly bonded to the substrate, avoiding the risk of film falling due to poor bonding between the film layer and the substrate after the introduction of the doping element, and the transition layer of this thickness is conducive to achieving wear-resistant properties.
[0040] In an exemplary embodiment, the hydrophobic layer 130 includes at least one doped DLC film layer with a thickness of 100nm-600nm, and the doped DLC film layer can be formed on a surface of the transition layer 120 away from the substrate 110 by using a CVD (Chemical Vapor Deposition) process. Since the doped DLC layer easily absorbs energy in the infrared band, the light transmittance can be ensured by reasonably setting the thickness of the hydrophobic layer.
[0041] Among them, the doped elements or materials in the doped DLC film layer can be selected from at least one of the following: F, Fe, Al, Cu, Ag, Sn, Si, Ti, Ge, and organic polymers.
[0042] In an exemplary embodiment, before forming the transition layer 120 on the surface of the substrate 110, the surface of the substrate 110 is pre-treated to form a disordered microstructure. The disordered microstructure is conducive to forming the hydrophobic surface morphology required by the subsequent film layer (including the transition layer, the hydrophobic layer, etc.), creating conditions for achieving the hydrophobic properties of the film layer.
[0043] In an exemplary embodiment, the protective layer 140 includes at least a DLC film layer with a thickness of 10nm-30nm. The DLC film layer is used as a protective layer to reduce the degree of modification of the F-Cx bonds on the surface of the hydrophobic layer 130 by the atmospheric environment, thereby protecting the hydrophobic layer 130. By providing a thin protective layer 140 on the outside of the hydrophobic layer 130, a certain degree of wear resistance can be achieved while maintaining the hydrophobic properties of the film.
[0044] According to another aspect of the present application, an optical lens is provided, which includes a lens substrate and an infrared highly hydrophobic film formed on the lens substrate. The infrared highly hydrophobic film may be the diamond-like film 100 provided according to the above-mentioned embodiment of the present application.
[0045] Combination Figure 2 As shown, according to another aspect of the present application, a method 200 for preparing a diamond-like film is provided, which can be used to prepare the diamond-like film 100 of the aforementioned embodiment. The preparation method 200 may include the following main steps:
[0046] S210, performing surface pretreatment on the substrate and forming a disordered microstructure on the surface of the substrate;
[0047] S220, forming an undoped DLC film layer with a thickness of 450nm-1200nm on the surface of the substrate;
[0048] S230, forming a doped DLC film layer with a thickness of 100 nm to 600 nm on the surface of the undoped DLC film layer;
[0049] S240, forming a DLC film layer with a thickness of 10 nm-30 nm on the surface of the doped DLC film layer.
[0050] In an exemplary embodiment, step S210 may specifically include: polishing the surface of the substrate to reduce the surface roughness of the substrate to the nanometer level (10nm-100nm); increasing the surface roughness of the substrate by laser etching and forming a disordered microstructure on the surface of the substrate; and pre-cleaning the surface of the substrate under vacuum conditions to eliminate impurities on the surface of the substrate and activate the surface of the substrate.
[0051] The above-mentioned disordered microstructure can be a nanoscale microstructure. By etching the disordered microstructure on the substrate surface, the hydrophobic surface morphology required for subsequent film layers (including transition layers, hydrophobic layers, etc.) can be constructed, which can create conditions for realizing the hydrophobic properties of the film layer without affecting the light transmittance of the film layer.
[0052] In an exemplary embodiment, a PECVD (Plasma Enhanced Chemical Vapor Deposition) process may be used in step S220, using hydrocarbon gases such as butane as reaction gases and inert gases such as argon as working gases to form an undoped DLC film layer as a transition layer on the surface of the substrate.
[0053] In an exemplary embodiment, the doped DLC film layer is a fluorinated DLC film layer, and a PECVD process can be used in step S230 to form a fluorinated DLC film layer as a hydrophobic layer on the surface of the transition layer using fluorine-containing gas and hydrocarbon gas as reaction gas and inert gas as working gas. The reaction gas can be carbon tetrafluoride (CF4), or SiH4, CHF3, CF3SiH3, CF3CH3SiH3 or other gases composed of elements such as F, Si and C; the hydrocarbon gas can be butane, acetylene or methane; and the inert gas can be argon.
[0054] In an exemplary embodiment, a PECVD process may be used in step S240 to form a DLC film layer as a protective layer on the surface of the fluorinated DLC film layer using acetylene, methane or butane as a reaction gas and argon as a working gas.
[0055] According to the diamond-like film and optical lens provided by the embodiment of the present application, by reasonably setting the structural design and thickness distribution of the film layer, the transmittance can be guaranteed while maintaining high hydrophobic performance, and it has certain wear-resistant properties. The transition layer can ensure that the film layer is firmly bonded to the substrate, and a transition layer with a certain thickness is conducive to achieving wear-resistant properties; at the same time, the thickness of the hydrophobic layer is reasonably set to ensure transmittance; by setting a thin protective layer outside the hydrophobic layer, the diamond-like film can have certain wear-resistant properties, improve wear resistance and weather resistance, and can improve adaptability and service life in harsh environments.
[0056] According to the diamond-like carbon film provided in the embodiment of the present application, the infrared hydrophobic DLC film is applied to the silicon / germanium / chalcogenide glass substrate through film layer design and preparation process; by doping with F elements (including but not limited to F, and can also be selected from Fe, Al, Cu, Ag, Sn, Si, Ti, Ge, organic polymers), the hydrophobic angle of the DLC film can be greatly improved, thereby reducing the degree of corrosion of the lens caused by liquid molecules such as water vapor in a humid environment, extending the service life of the lens, and ensuring the imaging quality of the lens.
[0057] According to the preparation method of the diamond-like carbon film provided in the embodiment of the present application, when the DLC film layer is doped with the F element, the F-Cx bond has strong absorption in the infrared band. Through the theoretical design of the film layer, on the one hand, the film thickness whose optical performance meets the requirements of the lens is simulated according to the optical constants of the film layer, and on the other hand, the doping amount of the F element is controlled to reduce the influence of the F-Cx bond on the transmittance of the film layer in the infrared band; at the same time, by pre-treating the substrate, optimizing the deposition process of the film layer, changing the surface morphology of the film layer, etc., the hydrophobicity of the DLC film is further improved, and the maximum hydrophobic angle can reach 120°, thereby increasing the service life of the lens.
[0058] Specific embodiments applicable to the above-mentioned embodiments are further described below with reference to the accompanying drawings and examples.
[0059] Embodiment 1
[0060] The present embodiment provides a Ge-based infrared hydrophobic diamond-like carbon film, which includes a transition layer, a hydrophobic layer and a protective layer plated on the surface of a lens substrate of a Ge-based material, wherein the transition layer is an undoped DLC film layer with a thickness of 500nm; the hydrophobic layer is a fluorinated DLC film layer with a thickness of 500nm; and the protective layer is a DLC film layer with a thickness of 20nm.
[0061] The preparation process of the diamond-like carbon film of this embodiment is as follows:
[0062] (1) Substrate surface treatment:
[0063] 1.1 Use a polishing process to reduce the surface roughness of the metal germanium substrate to the nanometer level, for example, the surface roughness is controlled to be less than 10nm;
[0064] 1.2 Use alcohol, detergent and pure water to ultrasonically clean the surface of the germanium substrate in turn to remove organic and inorganic dirt on the surface;
[0065] 1.3 The surface of the germanium substrate is processed by laser etching equipment. In order to avoid affecting the optical performance, the surface roughness is controlled at 15nm±5nm (10-20nm) and a disordered microstructure is formed.
[0066] (2) Surface pre-cleaning:
[0067] The substrate surface is checked to ensure that there is no dirt, and then placed in a PECVD coating machine for pre-cleaning. As an exemplary embodiment, the pre-cleaning is performed in an argon atmosphere with a power of 700-800 W, a bias voltage of 600-700 V, and a pre-cleaning time of 200 s.
[0068] The pre-cleaned substrate is not taken out but cooled for 120 seconds under vacuum conditions to avoid large thermal stress due to excessive temperature.
[0069] (3) Plating transition layer
[0070] After the substrate is cooled, a 500nm thick undoped DLC film is deposited using PECVD process with butane as the reaction gas and argon as the working gas. The undoped DLC film acts as a transition layer to avoid the risk of film falling due to poor bonding with the substrate after the introduction of F element.
[0071] As an exemplary embodiment, the flow rates of argon and butane during the coating process are 30 sccm (standard cubic centimeter per minute, volume flow unit) and 90 sccm, respectively. The power is fixed between 600-800 W using a radio frequency power supply, and the bias is compensated to 700-800 V using a DC bias compensation power supply to complete the coating process of the transition layer.
[0072] After the transition layer is deposited, the lens is naturally cooled for 100 seconds under vacuum conditions.
[0073] (4) Hydrophobic coating
[0074] After cooling, the lens is not taken out, and a fluorinated DLC film layer with a thickness of 500 nm is continuously deposited, and the fluorinated DLC film layer serves as a hydrophobic layer.
[0075] In the plating process, carbon tetrafluoride and methane are used as reaction gases, and argon gas is used as working gas. Exemplarily, the flow ratio of carbon tetrafluoride to methane is 8:1 to 11:1.
[0076] (5) Plating protective layer
[0077] As an exemplary embodiment, a PECVD process is used, butane is used as a reaction gas, and argon is used as a working gas to plate a DLC film layer with an outermost thickness of about 20 nm. Exemplarily, the flow ratio of argon and acetylene used in the plating process is 10sccm:30sccm. The DLC film layer acts as a protective layer, which can reduce the degree of modification of the F-Cx bond on the surface of the hydrophobic layer by the atmospheric environment, and plays a protective role on the hydrophobic layer.
[0078] Figure 3FIG. 2 shows the transmittance curve of infrared light of the Ge-based DLC film according to the first embodiment of the present application. Figure 3 As shown, through spectral measurement, the average transmittance of the Ge-based DLC film provided in Example 1 of the present application in the 8μm-12μm band is not less than 50%, wherein the wavelength corresponding to the maximum transmittance is in the range of 9.0μm-9.9μm.
[0079] Combination Figure 4 and Figure 5 As shown, the hydrophobic angle of the Ge-based infrared DLC film layer according to the prior art is generally about 65°, and the hydrophobic angle of the Ge-based DLC film according to Example 1 of the present application is about 86°, which is about 21° higher than the hydrophobic angle of the prior art.
[0080] In addition, according to the test results, the Ge-based DLC film provided in Example 1 of the present application has passed the bonding strength test (MIL-C-48497A), the salt spray test 168H (MIL-STD-810H para 509.7), and the high temperature and high humidity test 168H (MIL-C-48497A), and thus has excellent corrosion resistance and high temperature and high humidity resistance, meeting the performance requirements of the lens in extreme environments.
[0081] Embodiment 2
[0082] This embodiment provides an infrared hydrophobic diamond-like carbon film, which includes a transition layer, a hydrophobic layer and a protective layer formed in sequence on the surface of a substrate. The substrate material may be Ge / Si; the transition layer is an undoped DLC film layer with a thickness of 1100nm; the hydrophobic layer is a fluorinated DLC film layer with a thickness of 200nm; and the protective layer is a DLC film layer with a thickness of 20nm.
[0083] The preparation process of the diamond-like carbon film of this embodiment is as follows:
[0084] (1) Substrate surface treatment:
[0085] 1.1 Use polishing process to reduce the surface roughness of the substrate to <10nm;
[0086] 1.2 Use alcohol, detergent and pure water to ultrasonically clean the surface of the germanium substrate in turn to remove organic and inorganic dirt on the surface;
[0087] 1.3 The substrate surface is processed by laser etching equipment. After the processing, the surface roughness is controlled at 15nm±5nm (10-20nm) and a disordered microstructure is formed.
[0088] (2) Surface pre-cleaning:
[0089] Check the substrate surface to ensure it is free of dirt, then place it in the PECVD coater for pre-cleaning.
[0090] As an exemplary embodiment, the pre-cleaning is performed in an argon atmosphere with a power of 600-800 W, a bias voltage of 600-700 V, and a pre-cleaning time of 200 s.
[0091] The pre-cleaned substrate was not taken out and cooled under vacuum for 120 seconds.
[0092] (3) Plating transition layer
[0093] After the substrate is cooled, a 1100nm thick undoped DLC film is deposited using PECVD process with butane as the reaction gas and argon as the working gas. The undoped DLC film acts as a transition layer to avoid the risk of film falling due to poor bonding with the substrate after the introduction of F element.
[0094] As an exemplary embodiment, butane is used as a reaction gas and argon is used as a working gas during the plating process. The power is fixed between 600-800W by a radio frequency power supply, and the bias is compensated to 700-800V by a DC bias compensation power supply to complete the coating process of the transition layer.
[0095] After the transition layer is coated, the lens is cooled naturally under vacuum conditions.
[0096] (4) Hydrophobic coating
[0097] After cooling, the lens is taken out and placed in a hydrophobic layer coating device, and a fluorinated DLC film layer with a thickness of 200 nm is deposited using an IBS (Ion Beam Source) source. The fluorinated DLC film layer serves as a hydrophobic layer.
[0098] During the plating process, carbon tetrafluoride and acetylene are used as reaction gases, and argon is used as working gas, wherein the flow ratio of argon, carbon tetrafluoride and acetylene is 5 sccm:50 sccm:5 sccm.
[0099] (5) Ion bombardment
[0100] In this embodiment, optionally, after the coating process of the hydrophobic layer is completed, the surface of the fluorinated DLC film layer can be bombarded by an ion source to improve the surface roughness of the fluorinated DLC film layer. For example, argon gas can be used as a working gas, and high-energy argon ions can be formed by an ion source and a bias power supply to bombard the surface of the fluorinated DLC film layer. The ion source voltage during the bombardment process is 1100-1300V, the bias voltage is 650V±20V, the argon gas flow rate is 20-30sccm, the vacuum degree is 1-2Pa, and the bombardment time is 10min.
[0101] (6) Plating protective layer
[0102] As an exemplary embodiment, a PECVD process is used, butane is used as a reaction gas, and argon is used as a working gas to deposit a DLC film layer with an outermost thickness of about 20 nm. The DLC film layer serves as a protective layer.
[0103] It can reduce the modification degree of the F-Cx bond on the surface of the hydrophobic layer by the atmospheric environment and play a protective role on the hydrophobic layer.
[0104] Figure 6 FIG. 2 shows the transmittance curve of infrared band light of the infrared hydrophobic DLC film according to the second embodiment of the present application. Figure 6 As shown, through spectral measurement, the transmittance of the infrared hydrophobic DLC film provided in Example 2 of the present application in the 8μm-12μm band is ≥50%, and the average transmittance is 58.4%, wherein the wavelength corresponding to the maximum transmittance is in the range of 9.0μm-9.9μm.
[0105] like Figure 7 As shown, according to the prior art, the hydrophobic angle of the infrared DLC film layer is generally about 65°. Fig. 8A and Figure 8B According to the second embodiment of the present application, the maximum hydrophobic angle of the infrared hydrophobic DLC film can reach 120° to 121°, which is more than 50° higher than that of the prior art, thereby greatly improving the hydrophobic performance of the lens.
[0106] In addition, according to the test results, the infrared hydrophobic DLC film provided in Example 2 of the present application has passed the bonding strength test (MIL-C-48497A), the salt spray test 168H (MIL-STD-810H para 509.7), and the high temperature and high humidity 168H test (MIL-C-48497A), and thus has excellent corrosion resistance and high temperature and high humidity resistance, meeting the performance requirements of the lens in extreme environments.
[0107] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with the technical features with similar functions disclosed in this application (but not limited to) by each other.
Claims
1. A diamond-like carbon film, characterized in that: It includes a transition layer, a hydrophobic layer and a protective layer formed in sequence along the surface of the substrate. The transition layer at least includes an undoped diamond-like film layer, and the thickness of the undoped diamond-like film layer is 450nm-1200nm; The hydrophobic layer at least comprises a fluorinated diamond-like carbon film layer, and the thickness of the fluorinated diamond-like carbon film layer is 100 nm-600 nm; The protective layer at least includes a diamond-like film layer, and the thickness of the diamond-like film layer is 10nm-30nm; Wherein, the average transmittance of the diamond-like carbon film in the 8μm-12μm infrared band is ≥50%.
2. The diamond-like carbon film according to claim 1, wherein The substrate material includes germanium, silicon, or chalcogenide glass.
3. The diamond-like carbon film according to claim 1, wherein The fluorinated diamond-like carbon film layer is formed on the surface of the transition layer by using a chemical vapor deposition process.
4. The diamond-like carbon film according to claim 1, wherein The wavelength corresponding to the maximum transmittance of the diamond-like carbon film in the 8μm-12μm infrared band is in the range of 9.0μm-9.9μm.
5. The diamond-like carbon film according to claim 1, wherein Before forming the transition layer, a disordered microstructure is formed on the surface of the substrate.
6. The diamond-like carbon film according to any one of claims 1 to 5, wherein The hydrophobic angle of the diamond-like carbon film is 85°-120°.
7. A diamond-like carbon film, characterized in that: It includes a transition layer, a hydrophobic layer and a protective layer formed in sequence along the surface of the substrate. The transition layer at least includes an undoped diamond-like film layer, and the thickness of the undoped diamond-like film layer is 450nm-1200nm; The hydrophobic layer at least includes a doped diamond-like film layer, and the thickness of the doped diamond-like film layer is 100nm-600nm; The protective layer at least includes a diamond-like film layer, and the thickness of the diamond-like film layer is 10nm-30nm; Wherein, the average transmittance of the diamond-like carbon film in the infrared band of 8μm-12μm is ≥50%; The doped element or material in the doped diamond-like carbon film layer is selected from at least one of the following: Fe, Al, Cu, Ag, Sn, Si, Ti, Ge, and organic polymer.
8. An optical lens, comprising a substrate, and a diamond-like carbon film according to any one of claims 1 to 6 formed on the substrate.
9. A method for preparing a diamond-like carbon film, characterized in that: The method comprises: Performing surface pretreatment on a substrate and forming a disordered microstructure on the surface of the substrate; forming an undoped diamond-like carbon film layer with a thickness of 450 nm to 1200 nm on the surface of the substrate; forming a fluorinated diamond-like film layer with a thickness of 100 nm to 600 nm on the surface of the undoped diamond-like film layer; and A diamond-like film layer with a thickness of 10 nm to 30 nm is formed on the surface of the fluorinated diamond-like film layer.
10. The preparation method according to claim 9, wherein: The substrate material includes germanium, silicon, or chalcogenide glass.